2021
DOI: 10.1111/php.13481
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjunctive Antimicrobial Photodynamic Therapy to Mechanical Debridement in the Treatment of Peri‐implantitis or Peri‐implant Mucositis in Smokers: A Systematic Review and Meta‐analysis

Abstract: This systematic review and meta-analysis aimed to determine whether adjunctive use of antimicrobial photodynamic therapy (a-PDT) in peri-implant diseases improves clinical outcomes in smokers. An electronic search was performed in MEDLINE (through PubMed), Scopus, Cochrane Library, Embase, Web of Science and Google Scholar. The primary outcome measures were bleeding on probing (BOP) and pocket depth (PD). Plaque index (PI) was the secondary outcome. Four RCTs, (188 participants) comprised of 118 cigarette smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The findings of the current systematic review are broadly in agreement with the relevant sections of previous systematic reviews (Schwarz et al, 2015; Ramamauskaite et al, 2021; Shahmohammadi et al, 2022). Schwarz and colleagues reported that “alternative/adjunctive measures may improve the efficacy over/of conventional non‐surgical treatments at peri‐implantitis sites” (Schwarz et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the current systematic review are broadly in agreement with the relevant sections of previous systematic reviews (Schwarz et al, 2015; Ramamauskaite et al, 2021; Shahmohammadi et al, 2022). Schwarz and colleagues reported that “alternative/adjunctive measures may improve the efficacy over/of conventional non‐surgical treatments at peri‐implantitis sites” (Schwarz et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…However, this conclusion was based mainly on studies in which the adjunctive measures concerned antibiotic therapy and not restricted to chemical approaches as in the current systematic review. More recently, another systematic review and meta-analysis, which specifically investigated the adjunctive use of photodynamic therapy, reported a significant benefit in terms of both PD and plaque index at 3-month follow-up over mechanical debridement alone (Shahmohammadi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PDT does not result in scarring post-treatment and reduces the risk of recurrence [ 28 ], rendering it a highly promising therapeutic approach. While PDT has been explored as a treatment for p-iM [ 29 ], studies have confirmed its efficacy in this context [ 16 21 , 23 , 30 – 33 ]. However, there is still controversy regarding the effectiveness of PDT in improving certain indicators for pi-M patients due to variations in study populations, duration of irradiation, and the use of PSs.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of using lasers of various wavelengths in treating peri-implant diseases have been reported in several reviews, 28 , 29 , 55 , 56 , 57 , 58 , 59 but the outcomes of using diode lasers in the management of peri-implant mucositis was reported in 2 systematic reviews. 20 , 60 Both reviews 20 , 60 included studies that evaluated the adjunctive use of both photodynamic therapy and diode laser of different wavelengths and showed that both adjunctive therapies did not provide additional benefits, in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%